2010
DOI: 10.1074/jbc.m109.024844
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Calcineurin Inhibitor CN585 Has Potent Immunosuppressive Properties in Stimulated Human T Cells

Abstract: The Ca 2؉ /calmodulin-dependent protein phosphatase calcineurin is a key mediator in antigen-specific T cell activation. Thus, inhibitors of calcineurin, such as cyclosporin A or FK506, can block T cell activation and are used as immunosuppressive drugs to prevent graft-versus-host reactions and autoimmune diseases. In this study we describe the identification of 2,6-diaryl-substituted pyrimidine derivatives as a new class of calcineurin inhibitors, obtained by screening of a substance library. By rational des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
(61 reference statements)
0
27
0
1
Order By: Relevance
“…9, D-F). To further confirm these observations, we utilized the potent calcineurin inhibitor CN585, which interacts directly with calcineurin (27). Similar to CSA, treatment with CN585 dose-dependently reduced IL-1␤ secretion with a minimal effect on TNF␣ or LDH release (Fig.…”
Section: Calcineurin Inhibitors Suppress Activation Of the Lipotoxicmentioning
confidence: 99%
“…9, D-F). To further confirm these observations, we utilized the potent calcineurin inhibitor CN585, which interacts directly with calcineurin (27). Similar to CSA, treatment with CN585 dose-dependently reduced IL-1␤ secretion with a minimal effect on TNF␣ or LDH release (Fig.…”
Section: Calcineurin Inhibitors Suppress Activation Of the Lipotoxicmentioning
confidence: 99%
“…Sato et al (2009) have showed that CsA significantly increased the number of living cells in SNAP-treated RGC-5 cells in comparison to cell-permeable radical scavenger (TEMPOL) and general caspase inhibitor (Z-VAD-FMK) who partially protected RGC-5 cells against SNAP-mediated cell death. However, literature has reported several CsA-related side effects such as nephrotoxicity, gastrotoxicity, hypertension, hyperlipidaemia, neurophaties and diabetes type II (Takahashi et al 2009;Erdmann et al 2010). Therefore, there is a need for novel cytokine regulating -MPTP blockers with fewer adverse effects.…”
Section: Discussionmentioning
confidence: 94%
“…26 Thus, we sought to determine whether calcineurin indeed plays a role in their mechanism of action. To this end, we used several established calcineurin modulators such cyclosporin A, developed as an immuno-suppressant drug due to the crucial role that calcineurin plays in T-cell activation ( Figure 5).…”
Section: ■ Discussionmentioning
confidence: 99%